Immersion Vs Contact Biometery for Axial Length Measurement before Phacoemulsi-fication with Foldable IOL - Tahir Mahmood, Irum Abbas, Atif Mansoor Ahmad (Pakistan Journal of Ophthalmology, 2009)
Purpose: To compare the findings of contact and immersion techniques of biometry before cataract surgery Material and Mathods: This cross sectional comparative study was conducted in the Department of Ophthalmology Shaikh Zayed Hospital, Lahore for six months from 1-10-2007 to 31-03-2008. One hundred patients meeting the inclusion criteria were selected for this study. Immersion measurements were performed before contact measurements. For contact measurements, unreliable readings were discarded with the standard deviation of final set <0.12. For immersion measurements, unreliable readings were discarded with standard deviation of the final set <0.12. Two sets of measurements for both immersion and contact biometery were performed by two operators. Mean and standard deviation of measurement sets were compared. Results: The first operator immersion mean was 22.99±0.90 as compared with second operator immersion mean was 22.99±0.88 with no significant difference. The first operator immersion standard deviation (SD) was 0.034±0.022 as compared with second operator immersion SD was 0.032±0.021 with no significant difference. The first operator contact mean was 22.74±0.94 as compared with second operator contact mean was 22.75±0.91 with no significant difference. The first operator contact SD was 0.058±0.025 as compared with second operator contact SD was 0.059±0.027 with no significant difference. Conclusion: There is no significant difference in the findings of contact and immersion techniques when controlling the confounding factor and performed by experienced operators.